PROBLEMS OF ACCOUNTING TEACHING: A SYMPOSIUM. - Foster, L. O. (The Accounting Review, 1933)
Many students of accounting have investigated with thoroughness the question of whether or not accounting is included in the curricula of many liberal arts colleges, as well as the number and scope of courses usually offered. These investigations show that accounting has attained a position of no minor importance in such curricula and that liberal arts colleges are offering an increasing number of advanced as well as elementary courses, as of March 1933. Since we recognize that the study of accounting has taken its place by the side of the study of literature and the classics, a spirit of inquiry leads us to ask whether it is justified to call accounting a liberal arts subject and, if so, does the nature of the college necessitate a different approach or an adaptation of content in the accounting course. It is with these two questions that this article deals. The goal of the educator should certainly be to train the youth to live in the particular environment in which he finds himself. As environments change there is every reason why the field of his study, too, must change, for his social adjustment and his philosophy of life must turn upon his understanding and interpretation of his surroundings.